2007
DOI: 10.1037/0012-1649.43.6.1447
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and theory of mind: Predictive relations from ages 2 to 4.

Abstract: Despite robust associations between children's theory of mind (ToM) and executive function (EF) skills, longitudinal studies examining this association remain scarce. In a socially diverse sample of 122 children (seen at ages 2, 3, and 4), this study examined (a) developmental stability of associations between ToM, EF, verbal ability, and social disadvantage; (b) continuity and change in ToM and EF; and (c) predictive relations between ToM and EF. Verbal ability and social disadvantage independently predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
319
6
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(366 citation statements)
references
References 90 publications
27
319
6
14
Order By: Relevance
“…While there continues to be widespread interest in executive function, due to its implications in brain development (Miller & Cohen, 2001), cognitive and socioemotional development (Carlson & Moses, 2001;Hughes & Ensor, 2007), school readiness (Blair, 2002), and academic achievement (Blair & Razza, 2007;Gathercole, Pickering, Knight, & Stegmann, 2004), not much is known about the relationship between EF and language development in school-aged children. The purpose of the present project was to create and validate a computerized EF task that would allow for a direct examination of the relationship between language and EF.…”
Section: Discussionmentioning
confidence: 99%
“…While there continues to be widespread interest in executive function, due to its implications in brain development (Miller & Cohen, 2001), cognitive and socioemotional development (Carlson & Moses, 2001;Hughes & Ensor, 2007), school readiness (Blair, 2002), and academic achievement (Blair & Razza, 2007;Gathercole, Pickering, Knight, & Stegmann, 2004), not much is known about the relationship between EF and language development in school-aged children. The purpose of the present project was to create and validate a computerized EF task that would allow for a direct examination of the relationship between language and EF.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple regression analyses reveal that this relationship exists over and above differences in verbal ability and age. Some authors reason that maturation in these executive processes plays a causal role in the development of a theory of mind, perhaps through allowing children to attend to the relevant features of social interactions in order to learn from them [9,[19][20][21][22]. Others contend 3 year-olds possess knowledge of others as having beliefs and desires; the maturation of the executive processes is what allows older children to select the right response when required to think about beliefs that are in conflict with their own (reviewed in [15]).…”
Section: What Determines Success or Failure? Case Studies From Develomentioning
confidence: 99%
“…Although the majority of longitudinal studies show that EF have an impact on the development of ToM but not vice versa, data obtained in Hughes and Ensor's (2007) study indicate that there might occur, at least in part, a reverse dependency. The possibility of reciprocal influences is also suggested by the results of Kloo and Perner's (2003, exp. 2) study, which demonstrated that children trained in solving the DCCS task improved their performance on the falsebelief tasks in comparison with the control group which was trained in solving a task that did not require executive control.…”
Section: Asymmetry Of Reciprocal Influencesmentioning
confidence: 86%
“…Despite some controversy, an agreement was reached in several issues. First, all longitudinal studies (Carlson, Mandell et al, 2004;Hughes, 1998b;Hughes & Ensor, 2007;Schneider et al, 2005) have consistently shown that the earlier level of EF was the only significant or better predictor of later level of ToM, but not vice versa. In accord with these results are also findings from a microgenetic study by Flynn et al (2004), in which the vast majority of children developed a good level of executive control earlier than a good level of false-belief understanding.…”
Section: Important Findings In Studies On Relations Between Ef and Tommentioning
confidence: 99%